Legal Vacuum and Prudential Principles in MSME Financing under Article 249 P2SK Law - Ridlo, Ahmad Rayhan Thoha; Widhiyanti, Hanif Nur; Kusumaningrum, Adi (International Journal of Business, Law, and Education, 2026)
This study analyzes the legislative ratio of Article 249 of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK Law) in regulating MSME financing. Although the provision mandates easier access to financing for Micro, Small, and Medium Enterprises (MSMEs), it also requires the application of prudential principles and risk management practices. Normatively, the article does not clearly define the criteria for MSMEs eligible for financing, creating a legal vacuum and potential implementation inconsistencies. This research employs normative legal methods, drawing on statutory, conceptual, historical, and comparative approaches. The findings reveal a regulatory dilemma between financial inclusion and banking stability. The absence of standardised MSME financing criteria leads to disparities among financial institutions and increases credit risk exposure. The study proposes a prudential, proportional, and context-based financing model that emphasizes business sustainability, cash flow capacity, debtor integrity, and risk mitigation mechanisms to ensure inclusive yet stable financial system development.